1999
DOI: 10.1021/jo990616a
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active 11C-Labeled Amides Using Palladium-Mediated Reactions with Aryl Halides and [11C]Carbon Monoxide

Abstract: Using [11C]carbon monoxide in palladium-mediated synthesis, six amides were labeled with 11C. Phenyl and benzyl halides with halides as additional substituents were carbonylated and reacted with primary and secondary amines. Four of the selected amides were receptor ligands, one was a precursor to a receptor ligand, and one was a model compound. The 11C-labeled amides were obtained with good to almost quantitative radiochemical yields with specific activities up to 1000 GBq/μmol. The radiochemical purity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 21 publications
0
74
1
Order By: Relevance
“…[7,9] It was shown that yields with unreactive amines, such as anilines, may be increased by converting them into the corresponding lithium amides before carbonylation with [ 11 C]-carbon monoxide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,9] It was shown that yields with unreactive amines, such as anilines, may be increased by converting them into the corresponding lithium amides before carbonylation with [ 11 C]-carbon monoxide.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] A compelling, but not yet explored, synthetic route to such analogues is palladium-mediated carbonylation of aryl halides or triflates using [ 11 C]carbon monoxide. [7] We intended to use this approach to create a library of structurally related [carbonyl- 11 C]amides using amine 1 (Figure 1) and various aryl iodides. [8] However, the previously described procedure [7] provided only 0-15 % decaycorrected radiochemical yields of the amides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 15 A solution containing azidotrimethylsilane, [Rh(cod)Cl)] 2 , dppe and O-(trimethylsilyl)hydroxylamine in THF was transferred and pressurized to 35 MPa into the micro-autoclave. The reaction proceeded at 1208C for 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…5 This experimental setup had been successfully used to explore the reactivity of [ 11 12 and also in radical-mediated reactions. 13 All these methods permit the synthesis of 11 C-labelled compounds in high specific radioactivity in a range between 100 and 1500 GBq/mmol.…”
Section: Introductionmentioning
confidence: 99%